Methods and approaches for developing plain language versions of guidelines recommendations: Scoping review protocol - Friessová, Tereza; Langaufová, Alena; Dolanová, Dana; Beharková, Natália; Vrbová, Tereza; Búřilová, Petra; Pokorná, Andrea (Journal of evaluation in clinical practice, 2024)
AIMS AND OBJECTIVES: This is a protocol of a scoping review that will aim to synthesise methodological evidence on formulating plain language versions of recommendations from guidelines both for clinical practice and for public health. METHOD: We will conduct a search in MEDLINE (Ovid), Embase (Ovid) databases, and webpages of guidelines developers with no language and date limitations. The title/abstract and full-text screening will be performed by two reviewers independently. The team of reviewers will extract data on methods used for developing plain language versions of recommendations in a standardised manner. The data analysis and synthesis will be presented narratively in tabular form. RESULTS AND CONCLUSION: We will conduct a scoping review based on this protocol.
Keywords: decision making; language; practice; Humans; Language; Practice Guidelines as Topic; consumer health information; jazyk (prostředek komunikace); lidé; výzkumný projekt; health knowledge; health education; guideline as topic; Scoping Reviews As Topic; scoping review jako téma; směrnice pro lékařskou praxi jako téma; attitudes; Research Design